Preparation of Isotropic Carbon Fibers from Kerosene-Purified Coal Tar Pitch by Co-Carbonization with Pyrolysis Fuel Oil - Seon Ho Lee (MDPI AG, 2021)
An inexpensive and general-purpose carbon fiber was prepared using coal tar pitch. In contrast to the solvent extraction process employing expensive solvents, a low-cost centrifugal separation method facilitated the reduction of loss due to the pitch purification and an overall yield increase. The coal tar pitch purified by centrifugation and subsequently co-carbonized with pyrolysis fuel oil improved in spinnability. Moreover, the resulting spinnable pitch had a softening point of 250 °C. The obtained carbon fibers were heat-treated at 1000 °C for 5 min, resulting in a tensile strength of approximately 1000 MPa and an average diameter of 9 μm. In this study, we present an effective method for obtaining low-cost general-purpose isotropic carbon fibers.